Donor-Derived Tuberculosis: A Case Report and the Role of Communication Gaps in Transplantation Safety - Wanessa T. Clemente; Luciana C. Faria; Gláucia F. Cota; Leandro Ricardo de Navarro Amado; Jaqueline G. F. Oliveira; Silvana Spíndola de Miranda; Omar Lopes Cançado; Roberta M. C. Romanelli; Agnaldo S. Lima; Luiza Bastos Frade; Fernando Lucas; Marcelo Dias Sanches (Case Reports in Transplantation)
Donor-derived tuberculosis (DD-TB) accounts for less than 5% of TB cases and is considered a rare event. In the transplant setting, the frequency of active TB is estimated to be 20 to 74 times higher than that in the general population, and it is associated with high mortality. In this context, the main strategy to minimize the risk of DD transmission is to identify high-risk donors. Despite screening recommendations, failures may result in a breakdown of safety that ends in the transmission of potentially fatal diseases. This report describes a case of DD-TB and emphasizes communication gaps that may occur between organ procurement organizations and transplant centers. Failure in reporting results, lack of exchanging information regarding recipients from the same donor, and inefficient communication between organ procurement organizations and transplant centers are lacks that may be prevented by a more efficient approach towards screening protocols and communication.